Rating Iranian Banks According to their Financial Strength - Mohammad Javad Salim; Jafar Babajani; Abolfazl Jafari (مطالعات تجربی حسابداری مالی, 2017)
One of the essential needs of Iranian financial market participants (including money market and capital market participants) is rating Iranian banks based on their financial strength. This rating helps stakeholders, including shareholders, investors, customers, central bank and etc., to obtain more accurate information regarding inherent safety and soundness of Iranian banks. The aim of this study is rating Iranian banks, based on financial strength, specifically those listed on the Tehran Stock Exchange (TSE) and Iran OTC market. All the banks were separated into two groups of privatized and non-governmental banks. The period of the research is 5 years from 2012 to 2016. For this purpose, first a financial strength score was determined for each of the banks using a reflective component-based model which includes 4 dimensions, 8 factors and 51 indicators, Then the banks were ranked based on their financial strength scores in two separate groups of privatized and non-governmental banks. The results show that privatized banks compared with non-governmental banks have higher financial strength scores. In the group of privatized banks, Mellat Bank had the highest score and hence the highest rank in terms of financial strength. In the group of non-governmental banks, Pasargad Bank, EN Bank and Parsian Bank, respectively had the highest scores and hence the highest ranks in terms of financial strength.